Update on Viral Infections Involving the Central Nervous System in Pediatric Patients - Giovanni Autore; Luca Bernardi; Serafina Perrone; Susanna Esposito (MDPI AG, 2021)
Infections of the central nervous system (CNS) are mainly caused by viruses, and these infections can be life-threatening in pediatric patients. Although the prognosis of CNS infections is often favorable, mortality and long-term sequelae can occur. The aims of this narrative review were to describe the specific microbiological and clinical features of the most frequent pathogens and to provide an update on the diagnostic approaches and treatment strategies for viral CNS infections in children. A literature analysis showed that the most common pathogens worldwide are enteroviruses, arboviruses, parechoviruses, and herpesviruses, with variable prevalence rates in different countries. Lumbar puncture (LP) should be performed as soon as possible when CNS infection is suspected, and cerebrospinal fluid (CSF) samples should always be sent for polymerase chain reaction (PCR) analysis. Due to the lack of specific therapies, the management of viral CNS infections is mainly based on supportive care, and empiric treatment against herpes simplex virus (HSV) infection should be started as soon as possible. Some researchers have questioned the role of acyclovir as an empiric antiviral in older children due to the low incidence of HSV infection in this population and observed that HSV encephalitis may be clinically recognizable beyond neonatal age. However, the real benefit-risk ratio of selective approaches is unclear, and further studies are needed to define appropriate indications for empiric acyclovir. Research is needed to find specific therapies for emerging pathogens. Moreover, the appropriate timing of monitoring neurological development, performing neuroimaging evaluations and investigating the effectiveness of rehabilitation during follow-up should be evaluated with long-term studies.